Ponto de Tecer Vidas Ribeirinhas : identidade e prática profissional de professores na Bacia do Médio São Francisco - Mendes, Jacqueline Araújo Corrêa (2007)
This essay had its origin in the uneasiness lived on the everyday teaching work and on the interaction with teachers in their teaching formation. The necessity of deconstructing mistaken impressions on the teaching identity by unraveling the Geography teachers practice was the challenge of the theme here proposed. Thus, the traced plan had as goal to study how, in their day by day pedagogical practice and along the teaching formation process, 5th to 8th grade Geography teachers in public schools, on riverside towns, on the medium São Francisco basin, integrate and put into interaction the lores arising from their local culture and from their school culture. The theoretical subsidy, from several areas of knowledge, propitiated the profundity and comprehension of the identity, professional practice, teachers knowledge categories, contributing to give shape to the scientific production. The qualitative approach was used and for methodology we used the oral life story of eight teachers, from five municipalities of the São Francisco basin. After being transcript, the narratives were sent back to the teachers, who interfered in the sense of keeping the report or not. In order to better outline our research, we decided for clipping the narratives and inserting the necessary reflections along the text in order to achieve our goals. The analyses developed showed that in the reality researched the Geography teachers have plied different realities on their life story and along their formation until they took charge of their teaching profession, the teachers identity is influenced by the social and cultural school everyday routine, modifying their way of life and their professional life. The research also showed that the Geography teachers articulate their local cultural knowledge with the school culture in a practice interlaced by a lot of limitations originated from the school organization and from the investments on the teachers continued formation.